Emotional Intelligence of 11th Grade Students of Muhammadiyah High School 2 Sidoarjo: Kecerdasan Emosional Siswa Kelas 11 Sekolah Menengah Atas Muhammdiyah 2 Sidoarjo - Lutfidha, Bunga Pradany; Fahmawati, Zaki Nur (Journal of Islamic and Muhammadiyah Studies, 2023)
The purpose of this study was to describe the description of the emotional intelligence of class XI students of SMA Muhammadiyah 2 Sidoarjo during face-to-face learning after online learning due to the Covid-19 pandemic. The subjects in this study were class XI students, totaling 205 subjects with a description of how the emotional intelligence of class XI students was after online learning at home due to the Covid-19 pandemic. This research uses random sampling method. This research data collection tool uses a psychological scale, namely the emotional intelligence scale. This data analysis used descriptive statistics. The results of this study show that the emotional intelligence of class XI students of SMA Muhammadiyah 2 Sidoarjo is in the medium category but the percentage of female students has a higher score of 15% while the percentage of male students is 13%. Then for the highest emotional intelligence aspect value, namely managing one's own emotions by 29.94% and for the lowest emotional intelligence aspect value, namely recognizing other people's emotions by 11.57%. This shows that online learning at home can shape the process of emotional intelligence for students of SMA Muhammadiyah 2 Sidoarjo class XI